Aerobic and anaerobic capacity of adult and young professional soccer players - Angius, L.; Olla, S.; Pinna, M.; Mura, R.; Marongiu, E.; Roberto, S.; Piras, F.; Corona, F.; Milia, R.; Tocco, F.; Concu, A.; Crisafulli, A. (Sport Sciences for Health, 2012)
While VO2max has been widely investigated, there is few research on anaerobic capacity (AC) in soccer players. Previous studies reported that AC is age-dependent and that young individuals had lower AC compared with adults. Thus, we wondered whether AC would have proven more useful than VO2max in differentiating adult soccer players from young players. A total of 37 male athletes from a professional team were recruited and divided into two sub-groups: the adult (AD, n = 20) group, older than 19 years, and the young (YO, n = 17) group, ranged from 16 to 18 years. Each participant underwent an incremental test on a treadmill to assess maximal velocity (V max), anaerobic threshold (AT) and VO2max and a supramaximal exercise at a velocity 10 % higher than V max to measure AC. The AD group reached higher AT and VO2max with respect to the YO group (55.23 ± 4.65 vs. 51.48 ± 4.73 mL min-1 kg-1), whereas no difference was found in parameters related to the AC. In conclusion, young soccer players had the same AC as adult, but they displayed a lower VO2max. These findings indicated that AC in professional players is fully developed already when they are young while aerobic capacity is still to be developed.